Occupational selection in multilingual labor markets - Núria Quella; Sílvio Rendón (Institute for the Study of Labor (IZA), 2008)
In multilingual labor markets agents with high proficiency in more than one language may be selected into occupations that require high levels of skill in communicating with customers or writing reports in more than one language. In this paper we measure this effect in Catalonia, where two languages, Catalan and Spanish, coexist. Using census data for 1991 and 1996, and controlling for endogeneity of Catalan knowledge, we find that proficiency in speaking, reading and writing Catalan reinforces selection into communication intensive jobs/positions such as entrepreneurial, trade, and service activities; white-collar occupations; and permanent employment. Interestingly, the effect of language on occupational selection is stronger for women than for men.
urn:nbn:de:101:1-2008042104
Keywords: J24; 330; Occupational selection; language; labor markets; Berufswahl; Mehrsprachigkeit; Spanisch; Kommunikation; Arbeitsmarkt; Katalonien; Spanien